Avaliação dos efeitos morfológicos do sunitinib em lesões cancerizáveis induzidas com DMBA em bolsa jugal de hamster sírio dourado (Mesocricetus auratus) e análise metodológica retrospectiva dos 60 anos deste modelo experimental de câncer bucal - Souza, Fernanda Lopes de (2014)
Oral squamous cell carcinoma is among the six most common cancers in the world. For half of the diagnosed cases, oral cancer is a fatal disease, and those who survive often are disfigured and life quality becomes highly compromised. In this sense, one of the main allies for possible pharmacological therapy testing is the animal model, in this case, the hamster buccal pouch carcinogenesis model. This experimental model has been used with great success over the last 60 years. However the different protocols found in the literature sometimes have incomplete information. Thus, in the first part of this work we conducted a review of the animal model over the last 60 years, analyzing important technical parameters, such as: 1 The hamster strains used; 2 - The gender of animals; 3 - The age of the animals at the beginning of the induction protocol; 4 - The buccal pouch that was used for induction; 5 The different types of carcinogens used; 6 The concentrations of these carcinogens; 7 The solvents used to dilute the carcinogen; 8 - The number of applications per week; 9 - The different applying systems; and 10 - The length of the exposure protocol used to induce carcinogenic lesions or cancer. After this study, we used a modified carcinogenic model to induce precancerous lesions in the hamster buccal pouch mucosa. In this experimental model we tested a novel pharmacological alternative used to treat different types of cancers. Sunitinib is a multiple tyrosine kinase inhibitor that acts on endothelial cells and pericytes inhibiting the process of angiogenesis which is essential for tumor growth. The second study evaluated qualitatively and quantitatively the morphological effects that sunitinib had in precancerous lesions induced by DMBA in the hamster buccal pouch mucosa. Moreover we evaluate different clinical parameters of these animals. Our main results with respect to the second study were: 1 - Sunitinib was not able to reverse the decrease in body weight gain induced by DMBA; - 2 Sunitinib was able to inhibit tumor growth and ulceration induced by DMBA; 3 - Sunitinib was able to reverse the increase in epithelial rete ridges induced by DMBA. Thus, sunitinib can be considered an effective agent for chemoprevention, being an interesting alternative for further studies in a more advanced stage of oral cancer in the hamster buccal pouch or similar model.